2017
DOI: 10.1016/j.devcel.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

SINAT E3 Ligases Control the Light-Mediated Stability of the Brassinosteroid-Activated Transcription Factor BES1 in Arabidopsis

Abstract: SUMMARY The plant hormones brassinosteroids (BRs) participate in light-mediated regulation of plant growth, although the underlying mechanisms are far from being fully understood. In addition, the function of the core transcription factor in the BR signaling pathway, BRI1-EMS-SUPPRESSOR 1 (BES1), largely depends on its phosphorylation status and its protein stability, but the regulation of BES1 is not well understood. Here, we report that SINA of Arabidopsis thaliana (SINATs) specifically interact with dephosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 38 publications
3
134
1
Order By: Relevance
“…In our growth conditions, BES1 transcript levels were elevated at night while decreased during the day, as opposed to the BES1 protein that is stabilized during early day (Fig 3). Although COP1 has been reported to degrade phosphorylated BZR1 in darkness (Kim et al, 2014), and SINAT E3 ligases to degrade the dephosphorylated BES1 protein in the light Yang et al, 2017), a similar light-dependent degradation of these proteins was not observed in our study, highlighting that growth conditions strongly affect BES1/BZR1 stability. Although COP1 has been reported to degrade phosphorylated BZR1 in darkness (Kim et al, 2014), and SINAT E3 ligases to degrade the dephosphorylated BES1 protein in the light Yang et al, 2017), a similar light-dependent degradation of these proteins was not observed in our study, highlighting that growth conditions strongly affect BES1/BZR1 stability.…”
Section: A B Ccontrasting
confidence: 80%
“…In our growth conditions, BES1 transcript levels were elevated at night while decreased during the day, as opposed to the BES1 protein that is stabilized during early day (Fig 3). Although COP1 has been reported to degrade phosphorylated BZR1 in darkness (Kim et al, 2014), and SINAT E3 ligases to degrade the dephosphorylated BES1 protein in the light Yang et al, 2017), a similar light-dependent degradation of these proteins was not observed in our study, highlighting that growth conditions strongly affect BES1/BZR1 stability. Although COP1 has been reported to degrade phosphorylated BZR1 in darkness (Kim et al, 2014), and SINAT E3 ligases to degrade the dephosphorylated BES1 protein in the light Yang et al, 2017), a similar light-dependent degradation of these proteins was not observed in our study, highlighting that growth conditions strongly affect BES1/BZR1 stability.…”
Section: A B Ccontrasting
confidence: 80%
“…COP1, a dark-activated ubiquitin ligase, is able to capture and degrade phosphorylated BZR1 in darkness [85]. A group of SINAT E3 ligases, on the contrary, are involved in degrading nonphosphorylated BES1 protein in the light [86]. In addition to light-controlled protein abundance of BES1 and BZR1, recent studies demonstrated that light negatively regulates the transcriptional activity of BES1 and BZR1 [88][89][90]92].…”
Section: Lightmentioning
confidence: 99%
“…At the transcription level, it has been reported that PP2A phosphatases can promote BR signaling by dephosphorylating BES1 and BZR1, whereas 14-3-3 and BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) negatively regulate BR signaling by inhibiting the translocation of BES1 and BZR1 from the cytosol to the nucleus [81][82][83]. Besides, protein degradation of BES1 and/or BZR1 has been reported to be regulated by many factors, including an F-box protein MORE AXILLARY GROWTH LOCUS2 (MAX2), ubiquitin E3 ligases such as PLANT U-BOX40 (PUB40), CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) and SINA of Arabidopsis thaliana (SINATs), photoreceptors such as UV RESISTANCE LOCUS 8 (UVR8), CRYPTOCHROME1 (CRY1) and PHYTOCHROME B (PHYB), and an autophagy receptor DOMINANT SUPPRESSOR OF KAR2 (DSK2) [84][85][86][87][88][89][90][91][92][93]. Moreover, BES1 and BZR1 were reported to be oxidized by ROS (e.g., H 2 O 2 ) and reduced by a thioredoxin TRXh5 [94].…”
mentioning
confidence: 99%
“…Second, BR-responsive transcription factors such as BES1 and BZR1 interact with a diverse set of other factors to alter their DNA-binding characteristics and the target spectrum of the transcriptional response [85][86][87][88][89][90][91][92][93]. Moreover, protein abundance of BR-responsive transcription factors is influenced by autophagy [94], light [95], and strigolactone signalling, which connects BR signalling to the control of shoot branching imparted by the interaction of the transcription factors with MORE AXILLARY BRANCHES2 (MAX2), an F-box protein that promotes degradation in the proteasome [96]. In addition to this cross talk mediated by BIN2 and the BR-responsive transcription factors, recent work has also uncovered branching and integration points of BR signalling at the level of the plasma membrane, through which the BR receptor complex emerged as a key site for regulation of BR signalling strength, as well as signalling integration and outbranching.…”
Section: Br Signalling Is Intimately Connected To Other Growth-regulamentioning
confidence: 99%